Boronic Acid-Catalyzed Regioselective Koenigs–Knorr-Type Glycosylation - Shimada, Naoyuki; Sugimoto, Tomoya; Noguchi, Mao; Ohira, Chikako; Kuwashima, Yutaro; Takahashi, Naoya; Sato, Noriko; Makino, Kazuishi (Journal of organic chemistry, 2021)
Boronic acid-catalyzed regioselective Koenigs–Knorr-type glycosylation is presented. The reaction of an unprotected or partially protected glycosyl acceptor with a glycosyl halide donor in the presence of silver oxide and a low catalytic amount of imidazole-containing boronic acid was found to proceed smoothly, which enables construction of a 1,2-trans glycosidic linkage with high regioselectivities. This is the first example of the use of a boronic acid catalyst to initiate regioselective glycosylation via the activation of cis-vicinal diols in glycosyl acceptors.